Experimental flows through an array of emerged or slightly submerged square cylinders over a rough bed - Marina Oukacine (Nature Portfolio, 2021)
Measurement(s) velocity • depth of water Technology Type(s) particle-image velocimetry • ultrasonic velocimetry • ultrasonic transit time probe Factor Type(s) square cylinder immersion rate Machine-accessible metadata file describing the reported data: https://doi.org/10.6084/m9.figshare.13286915